Higher Education Leadership Development During the COVID-19 Pandemic: An Exploration of Online Learner Readiness - Kevan W Lamm; Alyssa Powell; L. Rochelle Sapp; Alexa Lamm (Journal of International Agricultural and Extension Education, 2022)
The COVID-19 pandemic precipitated profound disruptions across the higher education sector as institutions were forced to restructure entire systems and operate with significantly reduced resources. Most notably, many institutions were forced to transition to fully virtual instruction. The present study examined adult leadership development program participants’ perceptions of online learning readiness during the transition to a fully virtual training environment precipitated by the COVID-19 pandemic. A census of the 2020 LEAD21 class was taken, and perceptions of online learning readiness were collected via a retrospective pre- and post-test. Descriptive and inferential statistics were used. Respondents had the highest levels of agreement with computer and Internet self-efficacy and the lowest levels of agreement with learner control in an online context. A paired t-test was conducted to analyze the difference in perceptions of online learning readiness post-training and retrospective pre-training. A statistically significant increase was observed for overall online learning readiness, as well as for computer and Internet self-efficacy, learner control, motivation for learning, Internet communication self-efficacy, and self-directed learning. An implication from this finding is that the transition to fully virtual training resulted in increased online learning readiness across all dimensions. With new strains of COVID-19 emerging and the potential for ongoing restrictions for social interaction, online learning will continue to be an important aspect of the educational process. It is vital that higher education leaders consider individuals’ readiness to effectively engage in online training and instruction. Implications and recommendations for future research in practice in international contexts are provided.
Keywords: online learning readiness; higher education; leadership; virtual training; COVID-19